A study on consumer habits in the dietary supplements market - Nábrádi, Zsófia; Bánáti, Diána; Szakály, Zoltán (Applied Studies in Agribusiness and Commerce, 2020)
There has been a continuous increase in the proportion of consumers using dietary supplements worldwide. Evidence based on former surveys suggests that in Hungary more than half of the population buy at least one type of dietary supplement (hereinafter DS). By using secondary research, the authors of the present paper examine the demographic factors determining the consumption of DS on a global scale. Consumption of DS increases with age and is more frequent among women. Consumers with higher qualifications and income tend to buy products containing vitamins and minerals to a greater degree. In the vast majority of cases the purchase and consumption of DS is based on consumers’ personal preferences and decisions, rather than on their physicians’ advice. It has been found that a high percentage of DS consumers probably do not even need any extra nutrient intake. In our primary research (N=1000) the specific attitudes to and characteristics of DS consumption among Hungarian adults are analysed on the basis of on a nationally representative survey. First, we identify the most important reasons which encourage consumers to buy DS. Consumer awareness concerning DS with a particular vitamin and mineral content and of other sources is examined, and we also assess the consumption of the product which is the most popular. The current paper attempts to identify the outlets Hungarian consumers typically buy DS from, and also what resources they use to keep themselves informed about these products. Consumers who admittedly reported (regular) consumption of a certain kind of DS product 6 months prior to the survey are further examined in relation to certain additional issues. The results of our survey provide an accurate picture of the DS consumption habits of the Hungarian population.JEL CODE: I12, M31